PENGARUH IMPLEMENTASI TUJUAN KESELAMATAN PASIEN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT ROYAL PRIMA MEDAN - Barus, Irene; Faris, Salam; Ananda Lubis, Fajar Rezeki (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract: Introduction: Patient Safety Goals (PSGs) are mandatory standards established to improve the quality of healthcare services and are closely related to patient satisfaction. Objective to analyse the effect of implementing six PSGs on the level of satisfaction of inpatients at Royal Prima Hospital in Medan. Methods: A quantitative study with a cross-sectional design involving 150 inpatients selected through consecutive sampling from May to August 2025. The instrument was a structured questionnaire with 25 items (6 PSS variables with 3-4 items, patient satisfaction, five items) on a 1-5 Likert scale that had been validated on 30 respondents (r0.361, α=0.812). Data were categorised as binary with a cut-off of ≥75% for logistic regression analysis. Analysis used multiple linear regression and logistic regression. Results: The implementation of SKP had a significant effect on patient satisfaction (R=0.821; Adjusted R²=0.659; F=36.98; p0.001). Partially, effective communication was the dominant predictor (Wald = 8.32; p = 0.004; OR = 1.756), followed by a reduction in infection risk (p = 0.002), accuracy of identification (p = 0.010), high alert medication safety (p = 0.026), and fall prevention (p = 0.045). The certainty of location/procedure/patient was not yet significant (p = 0.068). Conclusion and suggestion: Effective communication is a dominant factor in improving inpatient satisfaction through the implementation of SKP.Keywords: Effective Communication; Patient Safety; Patient Satisfaction; PSGs